Effects of arm explosive power, hand–eye coordination, and concentration on students’ badminton skills - Wahari Abas; Gusril Gusril; Ahmad Chaeroni; Muhammad Arnando (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to examine the influence of arm muscle explosive power, hand–eye coordination, and training concentration on badminton playing skills among elementary school students. A quantitative approach with path analysis was employed to analyze both direct and simultaneous relationships among variables. The sample consisted of 30 male students aged 10–12 years selected through purposive sampling. Data were collected using performance-based tests and standardized instruments, including a medicine ball throw test, shuttlecock wall toss test, grid concentration test, and badminton skill tests (service, lob, and smash). The results showed that arm muscle explosive power (β = 0.664; p < 0.001), hand–eye coordination (β = 0.234; p = 0.045), and training concentration (β = 0.269; p = 0.023) had significant positive effects on badminton skills. Simultaneously, these variables explained 70.6% of performance variance (R² = 0.706). In conclusion, badminton performance is influenced by integrated physical, coordinative, and psychological factors, with explosive power as the dominant predictor.